2015
DOI: 10.1590/1679-78251638
|View full text |Cite
|
Sign up to set email alerts
|

Multi objective optimization of foam-filled circular tubes for quasi-static and dynamic responses

Abstract: Fuel consumption and safety are currently key aspects in automobile design. The foam-filled thin-walled aluminium tube represents a potentially effective material for use in the automotive industry, due to its energy absorption capability and light weight. Multiobjective crashworthiness design optimization for foam-filled double cylindrical tubes is presented in this paper. The double structures are impacted by a rigid wall simulating quasi-static and dynamic loadings. The optimal parameters under consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Figure 4 shows the correlation graph between the results of the experiment and the numerical simulation of aluminum-foam double-cylinder tubes with respect to displacement and crushing force. Table 1 shows the difference between the experiment and numerical simulation, which is similar to references [21][22][23]. From these results, it can be assumed that the developed FE models are competent for design optimization exploration.…”
Section: Validationsupporting
confidence: 55%
“…Figure 4 shows the correlation graph between the results of the experiment and the numerical simulation of aluminum-foam double-cylinder tubes with respect to displacement and crushing force. Table 1 shows the difference between the experiment and numerical simulation, which is similar to references [21][22][23]. From these results, it can be assumed that the developed FE models are competent for design optimization exploration.…”
Section: Validationsupporting
confidence: 55%
“…The validation results of foam-filled double circular tubes under quasi-static impact loading are presented by Djamaluddin et al [39]. They carried out the comparison between the numerical simulation and the experiment result and demonstrated the deformation patterns [40] and force-displacement curve [41] of numeric simulation and experiment result of foam-filled double cylindrical tube subjected to quasi-static loading [35].…”
Section: Model Validationmentioning
confidence: 98%
“…Zarei and Ghamarian [16] [17] showed that simulation of the crushing of composite structures is complex to run explicitly due to some uncertainties such as material model parameters instead of the real physics, badly tuned contact de nition, incorrect damping in the model, and mechanism of delaminating. Djamaluddina et al [18] studied the crashworthiness design for thin-walled aluminum foamlled circular tubes using nite-element analysis for empty and foam-lled double and single tubes under pure axial impact. They used some criteria, such as peak crushing force and speci c energy absorption, at di erent impact velocities under axial impact loadings.…”
Section: Introductionmentioning
confidence: 99%